Advances in geotechnical engineering the Skempton Conference : proceedings of a three day conference on advances in geotechnical engineering, organised by the Institution of Civil Engineers and held at the Royal Geographical Society, London, UK, on 29-31 March 2004 - Jardine, Richard, 1953-; Potts, D. M.; Higgins, K. G. (Thomas Telford, 2004)
Presents the proceedings of the Skempton Memorial Conference on Advances in Geotechnical Engineering. This two-volume set reprints the Royal Society of London's short biographical memoir on ansi-Professor Sir Alec Skempton, and reflects on his contributions to engineering geology, and other subjects. It is aimed at geotechnical engineers.